2017
DOI: 10.1016/j.ajpath.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Retinal Damage after Ocular Alkali Burns

Abstract: Alkali burns to the eye constitute a leading cause of worldwide blindness. In recent case series, corneal transplantation revealed unexpected damage to the retina and optic nerve in chemically burned eyes. We investigated the physical, biochemical, and immunological components of retinal injury after alkali burn and explored a novel neuroprotective regimen suitable for prompt administration in emergency departments. Thus, in vivo pH, oxygen, and oxidation reduction measurements were performed in the anterior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(164 citation statements)
references
References 31 publications
(17 reference statements)
10
146
2
6
Order By: Relevance
“…In addition, we used a small molecule inhibitor of colony stimulating factor 1 receptor (CSF1R) to perform a set of microglia depletion experiments to study the roles of microglia and peripheral monocytes in retinal repopulation. This study shows that peripheral monocytes are not only responsible for acute retinal inflammation after ocular injury (1,14), but that they contribute to the permanent remodeling of the neuroglia system by establishing a pro-inflammatory phenotype that may promote or contribute to neurodegeneration. These findings may be clinically important and can help us better understand the mechanisms by which patients with acute ocular injuries (chemical, surgical, or traumas) become susceptible to progressive neurodegeneration processes, such as progressive retina ganglion cell loss (glaucoma) (15) long after the injury has taken place.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, we used a small molecule inhibitor of colony stimulating factor 1 receptor (CSF1R) to perform a set of microglia depletion experiments to study the roles of microglia and peripheral monocytes in retinal repopulation. This study shows that peripheral monocytes are not only responsible for acute retinal inflammation after ocular injury (1,14), but that they contribute to the permanent remodeling of the neuroglia system by establishing a pro-inflammatory phenotype that may promote or contribute to neurodegeneration. These findings may be clinically important and can help us better understand the mechanisms by which patients with acute ocular injuries (chemical, surgical, or traumas) become susceptible to progressive neurodegeneration processes, such as progressive retina ganglion cell loss (glaucoma) (15) long after the injury has taken place.…”
Section: Introductionmentioning
confidence: 76%
“…Prolonged residency of activated monocytes in the retina can lead to progressive gradual neuronal damage and irreversible visions loss, which recapitulates the clinical picture of glaucomatous damage after anterior segment injury, and may appear clinically as loss of retina ganglion cells. Under normal intraocular pressure this can resemble glaucoma seen in patients with chemical injuries (39)(40)(41), and could explain the increased glaucoma susceptibility in patients that have suffered acute ocular injuries (2,3,14,15). In the setting of ocular injury, ramified CX3CR1 + cells from the bone marrow may occupy and engraft into the three distinct microglia strata, thereby co-existing with embryonically derived microglia, yet as we have shown in this study they have distinct pro-inflammatory phenotype.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The alkali-burn injured rat model of corneal neovascularization was used to identify the inflammatory and oxidative mechanism [18]. Additionally, the alkali-burn injured rat model of corneal injury was also taken to explore the retinal damage [19], the therapeutic effects of antagomir-21 [20] and the inflammatory fibrosis [21]. In the present study, the corneal neovascularization rat model was established using the alkali-burn, our results obtained that the in vivo model was highly reproducible, which provided meaningful instruction for further corneal neovascularization study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the IOP control in 80% of glaucoma eyes by intensive management, the final BCVA was <20/200 in 73.3% of eyes with glaucoma, which presents the possibility of irreversible damage to the optic nerve and retinal ganglion cell layer after ocular surface burn. In this regard, several animal studies investigated the mechanism by which anterior burn could inflict harm on the posterior segment of an eye 17,18 . These studies revealed that the posterior segment damage was not mediated by direct detrimental effect of chemical agent or altered pH which was effectively buffered by the anterior segment.…”
Section: Discussionmentioning
confidence: 99%